Postural stability and lower leg muscle activity during a diagonal single-leg landing differs in male collegiate soccer players with and without functional ankle instability - Shun Kunugi; Akihiko Masunari; Naruto Yoshida; Shumpei Miyakawa (Japanese Society of Physical Fitness and Sports Medicine, 2017)
The purpose of this study was to investigate postural stability and lower leg muscular activity in male collegiate soccer players with functional ankle instability (FAI), during a diagonal landing. Twenty-two male collegiate soccer players were divided into an FAI group (n = 11) and healthy control group (n = 11). Muscle reaction times for sudden ankle inversion were measured to evaluate neuromuscular control in the peroneus longus (PL), peroneus brevis (PB), tibialis anterior (TA), gastrocnemius lateral head (GL), and gastrocnemius medial head (GM). Time to anteroposterior stabilization (TTSAP), time to mediolateral stabilization (TTSML), and activity of these muscles during a diagonal single-leg landing was measured. Reaction times in the peroneus muscles were delayed in the FAI group, compared to the control group (PL: P < 0.01, PB: P = 0.02). TTSML was increased in the FAI group, compared to the control group (P = 0.02). Muscular activity of PL, PB, and TA were reduced in the FAI group, compared to controls, during a diagonal single-leg landing (PL: P < 0.05, from 87 ms pre-initial contact [pre-IC] to 108 ms post-initial contact [post-IC], PB: P < 0.05, from 180 ms pre-IC to 123 ms post-IC, TA: P < 0.05, from 65 ms to 203 ms post-IC). Male collegiate soccer players with FAI had increased TTSML and reduced muscle activity in PL, PB, and TA during diagonal single-leg landing. It is important for clinicians to assess the postural stability and function of the lower leg muscle activity, during rehabilitation after ankle sprains.